2013
DOI: 10.7455/ijfs.v2i1.134
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidants, their properties, uses in food products and their legal implications

Abstract: Oxidation decreases consumer acceptability of food by changing its organoleptic properties, destroying essential nutrients and producing toxic compounds. Antioxidants delay oxidation of lipids in foods as well in human systems. Studies reveal that synthetic antioxidants may trigger diseases in human when consumed over a certain concentration. The toxicological effects of synthetic food antioxidants have been the focus of controversy in recent years. There is scope to use natural antioxidants, present in many c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 65 publications
0
24
0
Order By: Relevance
“…The fact that PO + BHT has a lowest induction period value and protection factor than samples containing our natural plant extract might be attributed to it instability at elevated temperature. Chang et al (1977) and Thorat et al (2013) showed that BHT and BHA are quite volatile and easily decompose at high temperatures. The observed efficiency of the extract in prolonging induction time of palm olein as well as its good protection factors might be attributed to the phenolic antioxidants present in this extract.…”
Section: Rancimat Testmentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that PO + BHT has a lowest induction period value and protection factor than samples containing our natural plant extract might be attributed to it instability at elevated temperature. Chang et al (1977) and Thorat et al (2013) showed that BHT and BHA are quite volatile and easily decompose at high temperatures. The observed efficiency of the extract in prolonging induction time of palm olein as well as its good protection factors might be attributed to the phenolic antioxidants present in this extract.…”
Section: Rancimat Testmentioning
confidence: 99%
“…However, recent reports reveal their implication in many health risks, including cancer and cardiovascular diseases, and their use is becoming restricted in several countries (Iqbal et al 2008). In addition, according to Chang et al (1977) and Thorat et al (2013), BHA and BHT are quite volatile and easily decomposed at high temperatures. Today, the increasing consumer awareness of synthetic food additives and safety has prompted increase interest in the use of natural antioxidants as alternatives to synthetic antioxidants, because of their potential health benefits (Krishnaiah et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Antioxidants are a group of molecules or complex systems that are present in foods at low concentrations, compared to those of an oxidisable compound. In the light of their stability, antioxidants can act as electron donors to significantly delay, inhibit or prevent the oxidation of both substrates embedded in food matrices and biomolecules in eukaryotic cells, while being oxidised themselves (Choe & Min, ; Lobo et al ., ; Thorat et al ., ; Tomović et al ., ). Antioxidants are thought to promote health by scavenging reactive species that would ordinarily exert potentially harmful effects on cellular biomolecules, namely, DNA, proteins and lipids (Finley et al ., ).…”
Section: The Process Of Oxidation Free Radical Formation and The Rolmentioning
confidence: 97%
“…Therefore, various studies around the world have been conducted to find a method to overcome these problems (Hwanhlem, Ivanova, Haertle, Jaffres, & Dousset, 2017; Kuley et al, 2019; Tamkute, Gil, Carballido, Pukalskiene, & Venskutonis, 2019). Food oxidation can be overcome and delayed by adding antioxidant compounds in the food products (Thorat et al, 2013), while the growth of bacteria can be inhibited by adding antibacterial compounds (Fernandez‐Lopez, Zhi, Aleson‐Carbonell, Perez‐Alvarez, & Kuri, 2005). Therefore, valuable bioactive compounds that can exhibit both functions at a same time are needed.…”
Section: Introductionmentioning
confidence: 99%